Hypolipidemic activity of Piper betel in high fat diet induced hyperlipidemic rat - Thirunavukkarasu Thirumalai; Narayanaswamy Tamilselvan; Ernest David (Journal of Acute Disease, 2014)
Objective: To evaluate the hypolipidemic effect of Piper betel (P. betel) in high fat diet induced hyperlipidemia rat. Methods: The methanol leaf extract was tested for hypolipidemic effect in the albino rats at the selected optimum dosage of 250 mg/kg body weight and administered orally. Adult male albino rats of six numbers in each group were undertaken study and evaluated. Results: In group II animals, the activity levels of serum total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL) and very low density lipoprotein-cholesterol (VLDL) were significantly enhanced when compared to that of normal rat. Conclusion: It could be said that the methanolic leaf extract of P. betel exhibited a significant hypolipidemic effect.